Addressing Mental Health Literacy in a UK university campus population: Positive replication of a Canadian intervention. (August 2019) - Hunt, Sarah; Wei, Yifeng; Kutcher, Stan
Objectives: Mental health concerns on university campuses are increasing in the UK. Improving mental health literacy (MHL) for students may be a useful part of an integrated approach to effectively address these concerns. This study evaluated a previously demonstrated effective Canadian campus MHL resource in a UK student sample. Design: This cross-sectional study conducted on one UK campus reports on student's opinions about the impact of the Transitions (2nd edition) resource as well as applying a standard measure of MHL. Methods: Online survey using a convenience sample of students during semester 1 conducted over a 1-week period at a large UK university. Results: Use of Transitions (2nd edition) improved student self-reported mental health knowledge, decreased stigma and increased help-seeking intent. Significant ( p < .05) improvement in a standard MHL assessment was also found. Conclusions: These results suggest that the Transitions resource may be a helpful intervention in addressing student mental health in a UK university campus setting.